Efficacy of Low-Frequency Acupuncture Therapy Based on the Midnight-Noon Ebb-Flow Concept for Central Neurogenic Bladder: A Randomized Controlled Trial - Wang, Zhenjun; Zhou, Xuyan; Liu, Xinxing; Xia, Yuan; Zhou, Yan; Luo, Lingyun (Urology Journal, 2025)
Purpose: This study aims to investigate the therapeutic efficacy and complications of low-frequency acupuncture therapy based on the Midnight-Noon Ebb-Flow concept in central neurogenic bladder (CNB). Materials and Methods: This study was a prospective, randomized controlled trial. Sixty patients diagnosed with CNB without prior treatment were randomly divided into two groups: the control group (n = 30) was treated with basic rehabilitation training, and the treatment group (n = 30) was treated with basic rehabilitation training plus low-frequency acupuncture therapy based on the Midnight-Noon Ebb-Flow concept for 4 weeks. The fixed acupuncture points selected were: Sanyinjiao (bilateral), Zhongji (unilateral), and Diji (unilateral). The study compared pre- and post-treatment clinical curative effects, urodynamic indicators, urination status, the Neurogenic Bladder Symptom Score (NBSS), the Urinary Symptom Distress Scale (USDS), the World Health Organization Quality of Life Brief Inventory (WHOQOL-BREF), and the occurrence of adverse reactions and complications between the two groups. Results: The overall efficacy rate of 96.67% in the treatment group was significantly higher than that in the control group (86.67%) (P < 0.05). After treatment, the MBC, MFR, Pdet, DASUV, and WHOQOL-BREF scores significantly increased, while the RUV, DUF, DAUL, NBSS and USDS scores all decreased in both groups, with the treatment group showing significantly better results than the control group (P < 0.05). There was no statistically significant difference in adverse reactions and complication rates between the two groups (P > 0.05). Conclusion: Low-frequency acupuncture therapy based on the Midnight-Noon Ebb-Flow concept significantly improves bladder function and alleviates urinary difficulties in CNB, demonstrating good safety and considerable clinical applicability.